Teacher Experience of Using Podcast As Media In Teaching EFL Students' Listening Skills: A Narrative Inquiry In A Private Islamic Senior High School In Ciamis - Dewisejati, Lovian Puspita; Friatin, Lilies Youlia; Rohayati, Dedeh (Universitas Galuh, 2024)
This study discusses teacher’s experience of using podcasts to teach listening. A qualitative method with the type of narrative inquiry approach has been used in this research. Researchers used interviews to answer research objectives. An interview was conducted with a teacher using a semi-structured interview technique. The results of this study show that podcasts are comfortable media that are used anywhere in class or outside of class. Podcasts have the potential to be a good media for listening teaching strategy because it is easy to use. Also, it helps teachers to get available teaching material resources and transcripts while listening to native speakers which makes teaching more fun, and thereby it supports the listening and teaching-learning process. Podcasts are used effectively for teaching so that they have a positive impact on EFL students after teaching using podcasts is implemented. Students become confident and more sensitive to what is heard, and students' abilities improve, develop, and are stimulated when listening to native speakers. Podcasts are digital recording media that are distributed by the internet supply which is part of MALL language learning that allows users to study independently anywhere without time and place restrictions. MALL is a mobile-assisted language learning practiced by developing the use of technology to guide students and to benefit from the use of technology. Researchers also found the challenges of teaching students at the first time they used a podcast as well as the difficulties in teaching during the pandemic era. This study also provides suggestions for future researchers who have the same topic in more broadened insight.